Strengthening Industrial IoT Security: An Analytical Review of Cryptographic Techniques and Blockchain-Based Solutions - Fuad Hasan, Mochammad (Universitas Komputer Indonesia, 2023)
The Industrial Internet of Things (IIoT) has revolutionized traditional industrial systems by increasing connectivity, automation, and data-driven decision-making. However, this increased complexity also presents major cybersecurity-related challenges, including the threat of data breaches and operational disruptions. This study aims to provide an analytical review of cryptographic techniques and blockchain-based solutions in strengthening IIoT security. Combining bibliometric analysis and Systematic Literature Review (SLR), analyzing peer-reviewed articles published between 2016 and 2023 were analyzed. The bibliometric analysis revealed significant research growth trends, key contributions from global institutions, and emerging research themes such as lightweight cryptography, blockchain-based authentication, and secure communication models for resource-constrained IIoT devices. Meanwhile, the SLR provides an in-depth synthesis of the technical approaches, benefits, limitations, and open challenges in this field. The results show that the combination of cryptography and blockchain can offer decentralized, tamper-resistant, and efficient security solutions. The study also identified an urgent need for the development of more integrated and energy-efficient security models, as well as the validation of solutions in real industrial environments. The findings are expected to provide valuable guidance for the development of more reliable and secure IIoT systems in the future.